2003
DOI: 10.1034/j.1600-0714.2003.00162.x
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliative cytology of the oral mucosa in type II diabetic patients: morphology and cytomorphometry

Abstract: These results associated with clinical observations suggest that diabetes mellitus can produce alterations in oral epithelial cells, detectable by microscopy and cytomorphometry, which can be used in the diagnosis of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
92
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(109 citation statements)
references
References 12 publications
(16 reference statements)
13
92
2
2
Order By: Relevance
“…Several studies have reported the effect of different types of diseases and aggressive agents on oral mucosa, such as alcohol, and tobacco 10,12,[20][21][22][23][24][25] . However, studies reporting physical trauma associated to use of orthodontic appliances are still scarce 8 .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported the effect of different types of diseases and aggressive agents on oral mucosa, such as alcohol, and tobacco 10,12,[20][21][22][23][24][25] . However, studies reporting physical trauma associated to use of orthodontic appliances are still scarce 8 .…”
Section: Resultsmentioning
confidence: 99%
“…16 After NA and CA were measured, 11,12 the nuclear/cytoplasmic ratio (N/C) was determined for each cell. 11,14,17 …”
Section: Cytomorphometric Analysismentioning
confidence: 99%
“…Fifty cells on each slide were selected randomly for examination. [11][12][13][14] Areas with cells folded over and/ or clumped were avoided 15 because of the difficulty involved in determining cell boundaries. The image of the cytologic fields was captured at a magnification of 400 times ( Figures 3A through E) with the use of a Sony CCD Iris Color Video camera, model DXC-107A (Sony Electronics Inc, Tokyo, Japan).…”
Section: Cytomorphometric Analysismentioning
confidence: 99%
“…The most accepted clinical technique for the diagnosis of lesions in the oral mucosa is incisional or excisional biopsy (9). However, in specific clinical conditions, such as diabetes mellitus, a great many invasive techniques lose viability as a result of variations in blood glucose, infection, poor healing and the disease itself (10,11). In these cases, oral exfoliative cytology may be more appropriate (10).…”
Section: Introductionmentioning
confidence: 99%
“…However, in specific clinical conditions, such as diabetes mellitus, a great many invasive techniques lose viability as a result of variations in blood glucose, infection, poor healing and the disease itself (10,11). In these cases, oral exfoliative cytology may be more appropriate (10). Exfoliative cytology is a simple non-aggressive technique that is well accepted by the patient, and allows a quick and fairly accurate assessment of suspicious lesions of the oral cavity (12).…”
Section: Introductionmentioning
confidence: 99%